Mangrove ecocystem dynamics and elemental cycling at Twin Cays, Belize, during the Holocene - Wooller, M. J.; Behling, H.; Smallwood, B. J.; Fogel, M. (Journal of Quaternary Science, 2004)
Existing at the transition between the terrestrial environment and hydrosphere, mangroves are sensitive to environmental change (e.g. sea-level rise). We present pollen and stable isotope data from a core (TCC1) of continuous (10 m) mangrove peat from Twin Cays, ∼12 km off of the coast of Belize, Central America. Radiocarbon dates on fragments of mangrove leaves preserved in TCC1 show that the core provides an 8600 14C year record of mangrove ecosystem changes. Variation in the stable carbon and nitrogen isotope composition (δ13C = ∼−30 to −25‰; δ15N = ∼−6 to 2‰) of mangrove leaves imply that the stand structure and nutrient status of the mangroves at the site have changed during the Holocene. Pollen data from the same core show that the floral composition of the site has changed at points during the Holocene, most notably a brief (∼240 years) switch at ∼3860 14C yr BP to dominance by a species of Myrsine (not currently present at the site). Our results are consistent with significant environmental changes (either marked disturbance from hurricanes or fluctuations in sea-level) through the Holocene.
id: 1149
Keywords: Holocene; isotopes; pollen; mangroves; Palaeoecology